Reassuring one's friends: Richard Nixon's China policy and its impact on East and Southeast Asia, 1969-1974 - Ng, Sue Peng (2011)
This thesis is a study of how the Richard Nixon administration explained its China policy to its allies and friends in Asia and their reactions towards the major changes in the US-PRC relationship during the early 1970s. These allies and friends are the Republic of China (ROC), the Republic of Korea (ROK), Japan, the Philippines, Thailand, Indonesia, Malaysia and Singapore. When Nixon came to power in 1969, he was desperate to disengage from the Vietnam War and to reduce the United States (US) formal military presence in Asia. He employed the policies of Vietnamization and the Nixon Doctrine to achieve these objectives, which when combined with the US-PRC rapprochement would serve to reduce tensions in Asia. The Asian states were apprehensive of the future of the US commitment to the region due to the reduction of its military presence in Asia and their worries were compounded when Nixon sought rapprochement with the PRe. Explanations were sought from the US and reassurances were given by the Nixon administration in order to pacify its allies and friends in Asia. The development of the relationships of the Asian states with the PRC, and also with the US, revealed the extent to which Nixon was able to convince these Asian states that his China policy would not be detrimental to their security. The rapprochement did much to alter the relationships the Asian states shared with both the US and the PRC. Nixon's China policy acted as a catalyst for some of the Asia states to establish diplomatic relations with the PRC. These Asian states were either uncertain of the American commitment to Asia or recognised the convergence of interest between the rapprochement and their national interests. They then moved swiftly towards establishing diplomatic ties with the PRe.